Methadone: applied pharmacology and use as adjunctive treatment in chronic pain. Issue 949 (10th November 2004) - Brown, R; Kraus, C; Fleming, M; Reddy, S
Abstract : This article reviews the unique pharmacological properties of methadone and outlines its appropriate clinical application, with focus upon its use in the treatment of chronic pain. Although methadone is most widely known for its use in the treatment of opioid dependence, methadone also provides effective analgesia. Patients who experience inadequate pain relief or intolerable side effects with other opioids or who suffer from neuropathic pain may benefit from a transition to methadone as their analgesic agent. Adverse effects, particularly respiratory depression and death, make a fundamental knowledge of methadone's pharmacological properties essential to the provider considering methadone as analgesic therapy for a patient with chronic pain.